The lean toolbox : the essential guide to lean transformation - Bicheno, John, ....-; Holweg, Matthias, ....- (Buckingham : PICSIE books, 2009)
'The Lean Toolbox 4th Edition, the Essential Guide to Lean Transformation' is written for practitioners and for students, and is the extensively revised version of the best selling 'The New Lean Toolbox'. The book has sections on The Philosophy of Lean, Value and Waste, Transformation Frameworks, Deployment, Preparing for Flow, Mapping, Layout and Cell Design, Scheduling, TOC, Quality, Improvement, Managing Change, Sustainability, New Product Development, The Lean Supply Chain, and Accounting and Measurement.
Keywords: Lean management